2017
DOI: 10.1007/s40279-016-0655-1
|View full text |Cite
|
Sign up to set email alerts
|

Size Exponents for Scaling Maximal Oxygen Uptake in Over 6500 Humans: A Systematic Review and Meta-Analysis

Abstract: In this quantitative synthesis of published studies involving over 6500 humans, the whole body mass exponent was found to be spuriously low and prone to substantial heterogeneity. We conclude that the scaling of [Formula: see text] in humans is consistent with the allometric cascade model with an estimated prediction interval for the fat-free mass exponent not likely to be consistent with the [Formula: see text] power laws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 89 publications
2
63
0
Order By: Relevance
“…Currently, however, it is unknown whether children of higher body mass completing fewer shuttles is due to a lower aerobic fitness per se, or because they are carrying a higher body mass and therefore do more work in every shuttle. To elucidate this further would require a direct assessment of VO 2 peak Fitness Levels in Children From North East England scaled relative to an individual's body mass, or even fat-free mass (26), to be compared with 20mSRT performance, for example, which was beyond the scope of the current study. Participants' 20mSRT scores were distributed relatively evenly across the quintile scoring framework (43).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, however, it is unknown whether children of higher body mass completing fewer shuttles is due to a lower aerobic fitness per se, or because they are carrying a higher body mass and therefore do more work in every shuttle. To elucidate this further would require a direct assessment of VO 2 peak Fitness Levels in Children From North East England scaled relative to an individual's body mass, or even fat-free mass (26), to be compared with 20mSRT performance, for example, which was beyond the scope of the current study. Participants' 20mSRT scores were distributed relatively evenly across the quintile scoring framework (43).…”
Section: Discussionmentioning
confidence: 99%
“…Using power function modelling for scaling the VO 2 max Chia & Aziz (2008) revealed also different allometric factors for both sexes -b = 0.67 for male athletes and b = 0.24 for female athletes. The results of Lolli et al (2016) demonstrated lower exponent in women (b=0.52; 95% CL: 0.41 to 0.64) than for men (b=0.77; 95% CL: 0.71 to 0.83).…”
Section: Discussionmentioning
confidence: 80%
“…One of the factors explaining the significant differences in absolute oxygen uptake among groups of athletes with different BM, is the considerable heterogeneity of body composition (Lolli et al, 2016). Traditionally, sports scientists use the two-compartment model of body composition, which divides the body into two chemically distinct compartments -the fat mass and fat-free mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations